2006
DOI: 10.1051/0004-6361:20042331
|View full text |Cite
|
Sign up to set email alerts
|

Radio properties of FIR-megamaser nuclei

Abstract: Aims. Radio data on the nuclear emissions have been used to characterize the dominant nuclear activity in a sample of FIR (ultra-) luminous galaxies and the subgroup of known OH Megamasers. This study complements an earlier study of the optical classification of these Megamaser nuclei. Methods. Classification of the radio activity in the nuclei is based on three critical parameters: the radio brightness temperature, the radio spectral index, and the ratio of FIR and radio fluxes. A first method gives equal wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
92
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 39 publications
15
92
0
Order By: Relevance
“…Our data agree with previous observations with the VLA by Baan & Klöckner (2006). These authors detected the same total flux density in a similar beam, but did not discuss the structure of the emission, assuming the source to be unresolved.…”
Section: 4 Ghz and 5 Ghz Continuumsupporting
confidence: 91%
“…Our data agree with previous observations with the VLA by Baan & Klöckner (2006). These authors detected the same total flux density in a similar beam, but did not discuss the structure of the emission, assuming the source to be unresolved.…”
Section: 4 Ghz and 5 Ghz Continuumsupporting
confidence: 91%
“…Farrah et al (2003) found that this system is a composite object containing both starburst and AGN contributions, consistent with the result for its optical spectrum (Goncalves et al 1999). New evidence come from radiofrequencies where it is found a compact nucleus with flat spectral shape (Baan & Klockner 2006). The Fe-K emission is marginally detected in the analysis of Chandra data by Ptak et al (2003).…”
Section: Ugc 05101 (Iras 09320+6134)supporting
confidence: 73%
“…F.11). A compact flat spectrum radio source has been detected between 2 and 6 cm (Baan & Klockner 2006). At high X-ray energies only the northern nucleus is detected (Fig.…”
Section: Ugc 08696 (Mrk 273 Iras 13428+5608)mentioning
confidence: 93%
See 2 more Smart Citations